The determinants of economic growth in Malaysia / Nurul Nadiah Baharudin - Baharudin, Nurul Nadiah (2021)
This study attempts to study the determinants of economic growth in Malaysia for the period of 30 years from 1990 to 2019 using the time series data. Economic growth is important because it can support a country in terms of reduction in poverty, reduced unemployment, improved public services, and reduce debt to GDP ratios. The sets of data used for this study are Economic Growth (GDP) as the dependent variable and Foreign Direct Investment (FDI), Real Effective Exchange Rate (RER), Gross Capital Formation (GCF), and Trade (T) as the independent variables. A thorough comprehension of this topic will be useful not only for investors but also for future study. This study found that only FDI has a significant relationship with the economic growth while the other variables, RER, GCF and Trade has no significant relationship with the economic growth.